A unidirectional acoustic cloak for multilayered background media with homogeneous metamaterials. (3rd July 2015) - Zhu, Jian; Chen, Tianning; Liang, Qingxuan; Wang, Xiaopeng; Xiong, Jie; Jiang, Ping
Abstract: The acoustic cloak, which can make an object hard to detect acoustically in a homogeneous background, has attracted great attention from researchers in recent years. The inhomogeneous background media were considered in this paper. The relative constitutive parameters were derived for acoustic cloaks working in multilayered media. And a unidirectional acoustic cloak for layered background media was proposed, designed and implemented successfully in a wide frequency range. In water and NaCl aqueous solution, the acoustic cloak was designed and realized with homogeneous metamaterials which were composed of steel and porous materials. The effective parameters of the unit cells of the cloak were determined by using the effective medium theory. Numerical results demonstrated excellent cloaking performance and showed that such a device could be physically realized with natural materials which will greatly promote the real applications of an invisibility cloak in inhomogeneous backgrounds.